BIAYA IKLAN, INTENSITAS PERSEDIAAN, PERTUMBUHAN PENJUALAN DAN TRANSAKSI PIHAK BERELASI PADA AGRESIVITAS PAJAK: ADVERTISING COSTS, INVENTORY INTENSITY, SALES GROWTH AND RELATED PARTY TRANSACTIONS ON TAX AGGRESSIVENESS - Resty, Sefrilia; Yusralaini, Yusralaini; Rusli, Rusli; Wahyuni, Nita (Universitas Riau, 2024)
The research seeks to empirically investigate how Advertising Costs, Inventory Intensity, Sales Growth, and Related Party Transactions influence Tax Aggressiveness within the realm of Non-Cyclical Consumer Companies listed on the Indonesia Stock Exchange (IDX-IC Classification 2018-2022). The study targets non-cyclical sector consumer companies listed on the Indonesia Stock Exchange categorized under the IDX-IC classification from 2018 to 2022. The study utilised the multiple linear regression analysis approach to examine a sample of 15 organisations. The sample was picked via purposive selection and represented a total of 75 companies observed over a five-year period from 2018 to 2022. SPSS version 27 was utilized as the analytical tool. The research findings indicate that: (1) Advertising costs exert a significant influence on tax aggressiveness, evidenced by a significance level of 0.000 ≤ 0.05. (2) Inventory intensity also significantly impacts tax aggressiveness, as indicated by a significance level of 0.000 ≤ 0.05. (3) Sales growth, however, does not exhibit a significant effect on tax aggressiveness, with a significance level of 0.366 ≥ 0.05. (4) Similarly, related party transactions do not demonstrate a significant effect on tax aggressiveness, with a significance level of 0.109 ≥ 0.05.